Low-Profile Folded-Coupling Planar Inverted-F Antenna for 2.4/5 GHz WLAN Communications - Hung-Yu Li; Chun-Cheng Lin; Tsai-Ku Lin; Chih-Yu Huang (International Journal of Antennas and Propagation)
A dual-band folded-coupling planar inverted-F antenna (FC-PIFA) is presented in this paper. By using the folded-coupling technique, the proposed antenna provides two distinct impedance bandwidths of 159 MHz (about 6.5% centered at 2.45 GHz) and 1512 MHz (about 27.5% centered at 5.5 GHz), which cover the required bandwidths for the 2.4/5 GHz wireless local area network (WLAN) communications. Moreover, the antenna shows a low profile of 5 mm and a small length of 20.5 mm in radiating area, making it easy to be installed in the casing of wireless handheld devices and laptops. Details of the design procedures and experimental results are discussed.